2021
DOI: 10.1039/d1na00243k
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of PETase enzymes on magnetic iron oxide nanoparticles for the decomposition of microplastic PET

Abstract: Polyethylene terephthalate (PET) is responsible for a large part of environmental contamination with microplastics. Based on the high affinity, the PET degrading enzyme PETase can be immobilized on superparamagnetic iron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 56 publications
0
35
0
4
Order By: Relevance
“…When stored at 4 °C or room temperature for 30 days, BIND-PETase showed no significant change in enzyme activity (Figure S8A) (Student’s t test, p > 0.05). The storage stability of BIND-PETase surpassed the PETase enzyme immobilized on magnetic iron oxide nanoparticles, which had 40%–70% loss of its enzyme activity during 2 week storage at 4 °C . In addition, the whole-cell BIND-PETase biocatalyst could be recovered from the reaction solution by centrifugation and reused.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When stored at 4 °C or room temperature for 30 days, BIND-PETase showed no significant change in enzyme activity (Figure S8A) (Student’s t test, p > 0.05). The storage stability of BIND-PETase surpassed the PETase enzyme immobilized on magnetic iron oxide nanoparticles, which had 40%–70% loss of its enzyme activity during 2 week storage at 4 °C . In addition, the whole-cell BIND-PETase biocatalyst could be recovered from the reaction solution by centrifugation and reused.…”
Section: Resultsmentioning
confidence: 99%
“…The storage stability of BIND-PETase surpassed the PETase enzyme immobilized on magnetic iron oxide nanoparticles, which had 40%−70% loss of its enzyme activity during 2 week storage at 4 °C. 36 In addition, the whole-cell BIND-PETase biocatalyst could be recovered from the reaction solution by centrifugation and reused. The enzyme activity of BIND-PETase in pNPB hydrolysis retained 87.3% of the initial value after six repeated reaction cycles (Figure S8B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…62,71−76 Several published studies have explored PETase immobilization on metallic supports as a means of increasing stability by genetically fusing the enzyme to a metal-binding polyhistidine tag. 77,78 It has been shown that immobilization, even without introduction of spacer molecules to reduce steric hindrance, has the potential to enhance PETase activity and stability in harsh temperature and pH conditions 77,78 but the full scope of PETase immobilization has yet to be explored. Indeed, the majority of research on engineering PETase stability has focused on amino acid-level redesign of the free enzyme.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chromatographic product detection would have the additional benefit of enabling direct comparison between the presented data and previously published PETase engineering research. While we are not able to contextualize the data sets discussed in this paper in the broader literature context due to the differences in methodologies employed, the general trend of improved stability upon immobilization without detectable loss in activity holds true across other studies 77,78 To further challenge the chemical stability of the enzyme, free PETase−SBP and PETase−SBP•Si were incubated for 6 days at 40 °C in synthetic influent (Figure 5). In these conditions, both free PETase−SBP and PETase−SBP•Si retained activity for 72 h (Figure 5b).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation